Mineral Composition of Heavy Aggregates for Nuclear Shielding Concrete in Relation to Alkali-silica Reaction. (2015) - Jóźwiak-Niedźwiedzka, Daria; Gibas, Karolina; Brandt, Andrzej M.; Glinicki, Michał A.; Dąbrowski, Mariusz; Denis, Piotr
Abstract: The results of microscopic analysis on thin sections of aggregates intended for nuclear shielding concrete are presented. The petrographic analysis was performed on different barite, magnetite and hematite aggregates used as the high-density aggregate to absorb gamma radiation. Both optical microscopy and accelerated expansion tests were used to recognise the potential for alkali-reactivity of the aggregates. The mineral composition of the tested aggregates was analysed on thin sections in transmitted cross-polarized light and XRD tests were additionally performed. Expansion tests of mortar bars exposed to 1 N NaOH solution at the temperature of 80 °C were also performed following ASTM C1260. The high-density aggregates contained ore deposits - metallic opaque phases providing the required shielding properties. These aggregates also contained various amounts of non-metallic phases, with both innocuous non-ore minerals and deleterious, potentially reactive materials. Barite aggregates contained siderite, fluorite and hawleyite in varying amounts, apart from the barium sulphate being the principal component. Moreover, particularly reactive cristobalite and muscovite were identified in barite aggregates from certain quarries. Tests according to ASTM C1260 performed on mortars showed the expansion above the accepted criterion for non-reactive aggregate and confirmed the threat due to the presence of cristobalite in barite aggregates.